Maturasi Beragama: Studi Observasi Di Majlis Ta’lim Al-Muhibbien Kampung Elo, Desa Sukamanah, Kecamatan Sukatani - Bachtiar Bachtiar; Batubara, Noor Azidah; Zahro, S. Suaidatuz; Abdul, Hilya Maulida; Nuraini, Intan (JOURNAL SAINS STUDENT RESEARCH, 2026)
This study aims to explore the process of religious maturation within the Majlis Ta’lim Al-Muhibbien, located in Kampung Elo, Sukamanah Village, Sukatani District. This institution functions not only as a center for Islamic religious education but also as a form of social rehabilitation for individuals who have experienced drug addiction. Through in-depth interviews and observations of the majlis caretaker, Ustadz Abdul Kholik, as well as interactions with the students, the study finds that the process of religious maturity is cultivated through the strengthening of Islamic creed (aqidah), exemplary conduct, interreligious tolerance, and special mentoring for students from diverse social backgrounds.